2016
DOI: 10.3847/0004-637x/831/2/165
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Virgo Overdensity With Rr Lyrae Stars

Abstract: We use a combination of spatial distribution and radial velocity to search for halo sub-structures in a sample of 412 RR Lyrae stars (RRLS) that covers a ∼ 525 square degrees region of the Virgo Overdensity (VOD) and spans distances from the Sun from 4 to 75 kpc. With a friends-of-friends algorithm we identified six high significance groups of RRLS in phase space, which we associate mainly with the VOD and with the Sagittarius stream. Four other groups were also flagged as less significant overdensities. Three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 56 publications
3
63
0
Order By: Relevance
“…This N-body simulation is only a proof of concept, however; if this simulation were to be plotted on Figure 2, the bodies would significantly deviate from the positions of the orbit due to the size of the progenitor, and would not reproduce the correct sky positions for the moving groups. The simulation does show that it is possible to populate the range of distances and velocities of the Vivas et al (2016) RR Lyraes with one dwarf galaxy progenitor.…”
Section: The Virgo Radial Merger: a Common Origin For The Perpendiculmentioning
confidence: 94%
See 2 more Smart Citations
“…This N-body simulation is only a proof of concept, however; if this simulation were to be plotted on Figure 2, the bodies would significantly deviate from the positions of the orbit due to the size of the progenitor, and would not reproduce the correct sky positions for the moving groups. The simulation does show that it is possible to populate the range of distances and velocities of the Vivas et al (2016) RR Lyraes with one dwarf galaxy progenitor.…”
Section: The Virgo Radial Merger: a Common Origin For The Perpendiculmentioning
confidence: 94%
“…However, the single progenitor idea did not last. Duffau et al (2014); Vivas et al (2016) found several halo substructures along the same line of sight in Virgo. Zinn et al (2014) noted that the VSS was at the most distant part of the much larger VOD structure, but pointed to the large number of identified moving groups as evidence that the structure might not arise from a common origin.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hya 2 is a new detection. Crv 1 seems to be the southern extension to the Virgo Stellar Stream and G4 velocity complex discovered in [5]. Although at a similar location as the expected orbit of the Orphan Stream, Cen 3's distance and velocity do not correspond with the expected values in the area, representing then another new detection as well.…”
Section: Observations and Resultsmentioning
confidence: 72%
“…Although at a similar location as the expected orbit of the Orphan Stream, Cen 3's distance and velocity do not correspond with the expected values in the area, representing then another new detection as well. Confirmation of the results will be obtained by applying a group finding algorithm to the data, considering both the radial velocity of the stars and the separation between them, and simulating the Galactic contribution to assess the significance of these detections, as done in [1] and [5].…”
Section: Observations and Resultsmentioning
confidence: 99%